Avaliação dosimétrica durante procedimentos radiográficos em UTI pediátrica empregando simulação Monte Carlo - Silva, Daniela Carvalho (2021)
There is a concern about the radiation doses received early in life, as children are at high risk for developing diseases linked to radiation exposure. Chest and abdomen radiographs represent 75% of the diagnostic procedures performed while the newborns are admitted to a Neonatal Intensive Care Unit (NICU). In this work, typical NICU scenarios were constructed and two hermaphroditic pediatric anthropomorphic virtual phantoms were used, representing the examined newborn (NB) and the NB hospitalized in the neighboring bed. Computational simulation was used, with MCNPX 2.7.0 radiation transport code, to evaluate the equivalent and effective doses, 16 scenarios were simulated with the virtual phantoms inside the neonatal intensive care incubator, in the supine position, in the antero-posterior projection, with the mobile X-ray equipment, at a distance of 100 cm, and operating using the following tube voltages: 45 kV, 50 kV, 60 kV and 70 kV. The radiation field sizes used were: 18×24 cm², 24×30 cm², 30×30 cm² and 40×40 cm², anodic angle of 120 , total filtration of 2.3mmAl and 0.8 mm Be, and X ray tube with Tungsten target. The results showed that the effective dose increased as tube voltage increased, and this also occurred as the radiation field size increased; this fact happened for both newborns. The 18×24 cm² field size was responsible for the lowest dose values, and this demonstrates the importance of rigorous collimation. For the examined NB, the highest effective dose value was for the 40x40 cm² field size and 70 kV tube voltage, and the organs that received the highest equivalent dose values were skin, colon, thyroid, esophagus and bladder. The NB in the neighboring bed showed the result of an effective dose of 5.09E-03 µSv (1.41%), and according to the international recommendations is within the annual limits for members of the public (1 mSv/year); however it is recommended whenever possible to move the beds and/or move and protect the neonatal intensive care incubator in order to reduce the doses received.